Peran Insentif Transaksi Digital dan Kredibilitas Informasi dalam Mendorong Minat Pembelian Konsumen pada Platform Marketplace - Nissa Aurellia Puti; Sherena Anodhea Eka Pramudita (Journal of Economic and Business Advancement, 2025)
This study investigates the influence of free shipping, customer reviews, and cashback on purchasing decisions in marketplace platforms. The results demonstrate that free shipping significantly enhances consumer willingness to complete transactions because it removes additional costs and creates a perception of greater efficiency and value. Customer reviews play an essential role in shaping purchasing confidence by providing direct insights into product quality, helping reduce uncertainty, and guiding consumers toward more assured decisions. Cashback contributes to purchase motivation by offering immediate financial benefits, making each transaction feel more rewarding and encouraging stronger buying intentions. When examined collectively, the three variables show a more substantial impact than when analyzed individually, as their combined effect strengthens consumer trust, reduces decision-making barriers, and increases the perceived attractiveness of the purchase. These findings indicate that integrating cost-saving incentives, credible information, and financial rewards can effectively enhance marketplace competitiveness and improve consumer purchasing behavior.